Bazel I, II, III: the Development of Approaches for Strengthening of Prudential Framework - Науменкова, Світлана Валентинівна (Київський національний університет імені Тараса Шевченка, 2015)
У статті досліджено розвиток фундаментальних угод Базельського комітету з банківського нагляду (Базель ІІ, ІІ, ІІІ). Визначено перешкоди у запроваджені вимог Базеля ІІІ до капіталу банків в Україні в умовах посилення економічної нестабільності. Сформульовано пропозиції з підвищення ефективності пруденційної діяльності для відновлення стійкості банківського сектору України та попередження прояву регуляторного арбітражу.

The article is devoted to the analysis of the enhancement to the Basel III framework in the Ukrainian banking sector. The package of reforms offered by the Basel Committee on Banking Supervision is investigated. The author has defined the difficulties to implementation Basel III capital requirements to Ukrainian banking sector in conditions of growing economic instability. The rate of combined buffer requirements for Ukrainian banks' absorbing ability has been given more exactly. Out of minimum total capital was assessed to mitigate the systemic risks in the Ukrainian banking sector. The proposals for strengthening of prudential supervisory activity were suggested by author to raising the resilience of the financial system of Ukraine and prediction of regulatory arbitrage.
Базель І, ІІ, III: розвиток підходів для зміцнення регуляторної основи
Keywords: Базель І; ІІ; ІІІ; сукупні буферні вимоги; банківський нагляд; системний ризик; фінансова стійкість; Basel I; II; III; combined buffer requirements; banking supervision; systemic risk; financial sustainability